From the History of the First Medieval Culture of the Tashkent Event - F.E Toshboev; L.Z. Mamajonov (Genius Publishing Group, 2022)
In the early Middle Ages, significant, dramatic changes took place in the social, economic and political life of the peoples of Central Asia. Many migrations during this period created complex socio-political situations.In the existing agricultural oases of this period, the property of local, small khokimiyats, previously owned by a number of owners, was formed. Then, the development of these khokimiyats, which were nominally part of the great states of the early Middle Ages, the Hephthalites and the Great Turkic Khanate, flourished mainly in the context of political stability
Keywords: social; economic; political; states